Daya Terima Konsumen terhadap Inovasi Unik Produk Makanan Sambal Tabur Kecombrang - Laili Nabila Artanti, Hana; Ramadhani, Annisa Nurul; Nuzula, Zahra Firdausi; Rohmawati, Ovik Azahra; Gunalaing, Emiliana Siwu; Asmaul, Rina (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This research aims to determine consumers' acceptance of quality which includes taste and texture as well as packaging and price of the unique product innovation "Sambal Tabur Kecombrang" and determine the suitability of consumer tastes for sambal tabur kecombrang. Variable The population of this study was 50 respondents. This research uses the classic assumption test in the form of the normality test. The research results on the acceptance of unique innovations on consumer power have a good and significanteffect on product innovation development decisions. Quality and price have a positive impact on product innovation among consumers. Based on this test, it is known that the quality and price provided have a good impact and are well received by consumers of "Sambal Tabur Kecombrang". This Sambal Tabur Kecombrang is produced by students from Surabaya who are developing the latest breakthroughs in how to consume a product. Therefore, this research is very useful for producers as an evaluation material and product standard so that it can be maintained as an identity and ensure consumers continue to consume Sambal Tabur Nusantara with an authentic taste.